Angel on my shoulder : an autobiography - Cole, Natalie, 1950-; Diehl, Digby (New York : Warner Books, 2000)
The singer shares her tale of triumph over drugs, depression, divorce, and all the worst celebrity can bring
Includes discography (p. [333]-345) and index.
Keywords: Cole, Natalie, -- 1950-; Singers -- United States -- Biography